(untitled) (Revista Espaço Pedagógico, 2017)
Art materializes heightened experiences of transformation that depict human commonalities and particularities through imagery, thereby bringing understanding of self and of different worldviews and practices. This paper will present a conceptual framework based on theories of Ken Wilber, Ellen Dissanayake, and Suzi Gablik that promote the understanding of human commonalities and differences and how this framework relates to art. Wilber’s constructs of deep and surface structures of human consciousness account for modernista notions of commonalities and universalities and postmodern ideas of differences, contexts, and particularities. Dissanayake posits that art is a natural or innate human behavior that contributes to the survival of the human species. Gablik theorizes that there is need for change through art.